Ribosomal RNA precursors of Bacillus subtilis. - Loughney, K (1983)
The DNA sequence of the region corresponding to the 5'-end of a 16S rRNA gene of B. subtilis 168 was determined. Comparison of this sequence with the sequences flanking other 16S and 23S rRNA coding regions (1-4) indicated that large RNA stem structures, surrounding the mature 16S and 23S rRNAs, could form in a precursor rRNA. The 5'-ends of the precursors of 16S and 23S rRNAs (p16S and p23S) were mapped to the middles of these potential RNA stem structures. We propose that the initial cleavages of the primary rRNA transcript occur near the "opposed G's" which interrupt the basepairing of each of these stem structures. This model is supported by the finding that the 5'-end of the 5S rRNA precursor, p5A (5), maps to the region of the "opposed G's" in the 23S rRNA stem structure.